Highly sensitive lateral flow test with indirect labelling for zearalenone in baby food. Issue 1 (1st January 2020) - Bartosh, Anastasiya V.; Urusov, Alexandr Е.; Petrakova, Alina V.; Kuang, Hua; Zherdev, Anatoly V.; Dzantiev, Boris B.
ABSTRACT: Maximum permissible levels of mycotoxins in baby food may be 1% of those in ordinary food. Therefore, highly sensitive methods of mycotoxin control are in demand. To detect such low amounts, expensive instrumental methods are commonly used. Advantages of immunochromatographic analyses are their low cost and simple sample preparation; however, their sensitivity needs to be increased to contend with instrumental methods. A scheme for competitive immunochromatography with indirect labelling was implemented and developed for the detection of mycotoxin zearalenone (ZEA). Two separate reagents were used for the assay, namely free specific antibodies and antispecies antibodies conjugated with gold nanoparticles. This made it possible to simultaneously increase the sensitivity of the assay and the reliability of measurements. The instrumental detection limit of ZEA in baby food was 5 pg/mL (100 pg/g). Thus, the sensitivity attained is comparable with liquid chromatography characteristics. The duration of the analysis was 17 min.